Quantum leadership: new approach in managing shoulder dystocia in simulation-based training - Georges Yared; Christopher Massaad; Kariman Ghazal (Future Science OA)
Background Shoulder dystocia, a challenging condition for obstetricians, poses significant risks to both maternal and neonatal health, including maternal postpartum hemorrhage, neonatal hypoxia, and brachial plexus injury. Despite being unpredictable and unpreventable, effective management can mitigate these risks. Miscommunication and poor leadership are responsible for 72% of medical errors, which further highlights the importance of robust leadership skills in obstetric emergencies.Research design and methods A qualitative study involving 20 participants through structured interviews assessed preferred leadership styles in managing shoulder dystocia.Results Findings revealed that 55% of participants favored quantum leadership. Other preferences included laissez-faire by one anesthesiologist and democratic by two midwives. However, all participants acknowledged the efficacy of the seven quantum leadership skills in managing shoulder dystocia. Discussion emphasized that traditional leadership styles are less effective compared to quantum leadership in managing the complexities of shoulder dystocia. The quantum Ob-Wheel, consisting of 12 milestones, integrates these seven interdependent skills to guide the management process.Conclusions Despite the limited sample size of this study, it is worth noting that, given the unpredictable nature of shoulder dystocia, clinicians should be prepared for its occurrence during any birth, with quantum leadership providing a strategic advantage in such scenarios.